Emancipação e população escravizada no cenário do Brasil oitocentista (1870-1880). - Andrade, Maria Betânia Barbosa de (2024)
This work intends to present a reflection on the concept of emancipation used in the second half of the 19th century when discussing the emancipatory process for the enslaved population and the propositions for minor children, in light of Law nº 2040, of September 28, 1871, in order to elucidate whether it was linked to the political, economic, social and cultural context of the period or aimed at ensuring the needs of enslaved people were met. To do this, we use the work of Reinhart Koselleck, Marcelo Gantus Jasmin and João Feres Júnior, who point out the dimensions of the history of concepts and their use. From this perspective, we present some political, economic, social and cultural issues in nineteenth-century Brazil, based on José Murilo de Carvalho, Marcus J. M. de Carvalho and Sidney Chalhoub. Considering the theoretical and historiographical discussion, we relate the debates undertaken by representatives of social and political groups of the time (liberal and conservative) with the sources (propositions and texts from the Diario Novo newspapers dated 1840, O Liberal Pernambucano from 1850 and the Diario de Pernambuco dated from the 1870s to the year 1880), researched at the Biblioteca Brasiliana Guita and José Mindlin (BBM Digital), at the Digital Library of the Chamber of Deputies, at the Digital Library of the Federal Senate and at the Hemeroteca Digital Brasileira. The format of the study product is a booklet, as it constitutes teaching and educational material.